2001
DOI: 10.21273/hortsci.36.6.1085
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Adjuvant with Halosulfuron Affects Purple Nutsedge Control and Nursery Crop Tolerance

Abstract: One-half (18 g·ha-1 a.i.) and three-fourths (27 g·ha-1 a.i.) rates of halosulfuron (Manage®, MON 12051) were combined with adjuvants and evaluated for effectiveness in controlling purple nutsedge (Cyperus rotundus L.) and for phytotoxic responses exhibited by two kinds of container-grown ornamental plants. Adjuvants included X-77®, Scoil®, Sun-It II®, Action “99”®, and Agri-Dex®. By 8 weeks after treatment (WAT), halosulfuron combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The effectiveness of the foliar-applied herbicides on target weeds is highly affected by the type of adjuvant added into formulation [ 20 , 21 ]. On the other hand, the addition of adjuvants can alter the selectivity of chemical herbicides and NPDHs which in turn can lead to the decrease in crop tolerance [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of the foliar-applied herbicides on target weeds is highly affected by the type of adjuvant added into formulation [ 20 , 21 ]. On the other hand, the addition of adjuvants can alter the selectivity of chemical herbicides and NPDHs which in turn can lead to the decrease in crop tolerance [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Halosulfuron is an acetolactate synthase (ALS)-inhibiting (EC 4.1.3.18) sulfonylurea herbicide that is used to selectively control perennial sedge species, such as purple (Cyperus rotundus L.) and yellow nutsedge (Cyperus esculentus L.), and select broadleaf weeds in agronomic and horticultural crops and ornamental landscapes (Anonymous 2002b;Atland et al 2000;Haar et al 2002;McDaniel et al 2001;Whaley and Vangessel 2002). Halosulfuron also has been developed for the turfgrass market for postemergence control of yellow and purple nutsedge, Kyllinga spp., and other sedge species (Anonymous 2002a;Belcher et al 2002).…”
mentioning
confidence: 99%
“…Furthermore, some researchers reported the strong effect of mineral and vegetable oil on clodinafop-propargyl and diclofopmethyl + fenoxaprop-p-ethyl on Lolium multiflorum, Avena ludoviciana, and Phalaris minor [89]. Seed-oil-based crop oils and organosilicone adjuvants combined with halosulfuron lead to 100% control of Cyperus rotundus L. at 8 weeks after treatment (WAT) compared with a combination of halosulfuron with the nonionic or paraffinbased crop oil adjuvants (<90% control) [90]. The measurement of ED 50 and ED 90 showed that Citogate (0.1 and 0.2%) increased sulfosulfuron efficacy [91].…”
Section: Review Of Research On the Positive Effects Of Adjuvants Mixt...mentioning
confidence: 99%